Twenty Years of Thinking about Traumascapes. Issue 1 (2nd January 2019) - Tumarkin, Maria
ABSTRACT: I have been researching and writing about traumascapes for the past two decades. The central argument guiding my research is simple: physical sites of violence and loss are much more than mere backdrops to the traumatic events that take place in their soil. They are deeply implicated in individual and collective processes of grieving, remembering, and meaning-making. I deploy an autoethnographic approach in this paper, charting my progression through key ideas informing my research, and exploring in depth the dominance of the memorialisation trope in the majority of sustained engagements with places of trauma. I reflect on several recent cultural shifts that have been instrumental in changing our understanding of and relationship with physical sites of trauma, including the mainstreaming of grief's public life (once wild and uncontained spontaneous memorials, for example, are now culturally expected, almost mandated, in the West), the resolute everywhereness of traumascapes, the gradual depathologisation of trauma in public conversations and cultural imaginings, and a quiet revolution in the way we do memorialisation. I tentatively propose the next stage in imagining the future of sites inscribed with violence and loss, arguing for the necessity of superseding the idea of traumascapes in human engagement with such places.